1980
DOI: 10.1128/iai.29.1.108-113.1980
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Escherichia coli enterotoxins in stools

Abstract: We determined whether enterotoxigenic Escherichia coli diarrhea could be diagnosed by direct examination of stools for heat-labile (LT) and heat-stable (ST) enterotoxins. The Y-1 adrenal cell and an enzyme-linked immunosorbent assay (ELISA) detected LT in 85 and 93%, respectively, of stool specimens obtained from adults with acute diarrhea from whom an LTand ST-producing organism had been isolated. Furthermore, the ELISA assay detected LT in 8 of 35 stool specimens from which no LT-producing E. coli had been i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1981
1981
1996
1996

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…The standard assays for enterotoxin are overdue for improvements. Although several investigators have shown other methods to be feasible (10,12,14,16,17), the YAC assay remains the standard assay. Pooling of culture supernatants derived from isolated E. coli has been the standard method for screening samples for enterotoxin production.…”
Section: Discussionmentioning
confidence: 99%
“…The standard assays for enterotoxin are overdue for improvements. Although several investigators have shown other methods to be feasible (10,12,14,16,17), the YAC assay remains the standard assay. Pooling of culture supernatants derived from isolated E. coli has been the standard method for screening samples for enterotoxin production.…”
Section: Discussionmentioning
confidence: 99%
“…When the suckling mouse assay was used to detect ST. directly in stools, ST was found in only 36% of the cases from which ST-producing E. coli strains were isolated (17). With a more sensitive assay, the percentage of ST detection will probably increase substantially.…”
Section: Discussionmentioning
confidence: 99%
“…Examples of toxins that have been detected directly in stools from infected patients include Clostridium difficile toxin A (reviewed in reference 271), Shiga toxin (324), CT (reviewed in reference 383), and the heat-labile (LT-I) and heat-stable (STa) toxins from enterotoxigenic E. coli (ETEC) (365). How-ever, failure to detect toxins in stools may be due to the insensitivity of the detection assay, the toxin-binding effects of free gangliosides present in mucin found in stools, proteolytic degradation of the toxin in the intestinal tract, or other reasons.…”
Section: Introductionmentioning
confidence: 99%